2017
DOI: 10.1002/dneu.22567
|View full text |Cite
|
Sign up to set email alerts
|

LINE‐1 retrotransposons in healthy and diseased human brain

Abstract: Long interspersed element-1 (LINE-1 or L1) is a transposable element with the ability to self-mobilize throughout the human genome. The L1 elements found in the human brain is hypothesized to date back 56 million years ago and has survived evolution, currently accounting for 17% of the human genome. L1 retrotransposition has been theorized to contribute to somatic mosaicism. This review focuses on the presence of L1 in the healthy and diseased human brain, such as in autism spectrum disorders. Throughout this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 250 publications
(305 reference statements)
0
59
0
Order By: Relevance
“…The retrotransposons in Class I can be mainly divided into three groups of TEs, including LINE, LTR and SINE; and each group contains several subgroups. Retrotransposons, particularly L1, Copia, DIRS, ERV1, Gypsy, Pao, Alu and so on, are the easiest ones to be annotated, which are also the most abundant transposons in fungi (Suarez et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The retrotransposons in Class I can be mainly divided into three groups of TEs, including LINE, LTR and SINE; and each group contains several subgroups. Retrotransposons, particularly L1, Copia, DIRS, ERV1, Gypsy, Pao, Alu and so on, are the easiest ones to be annotated, which are also the most abundant transposons in fungi (Suarez et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Although, in some cases, transposon activation is known to cause genetic disorders and autoimmune reactions (44), however, they also play important "positive" roles in adult and developing tissues. For example, in mammalian neurogenesis retrotransposition activity of LINE-1 elements contributes to neuronal diversity (45,46). We have also recently shown that retrotransposons are differentially expressed in the sea cucumber neural regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…For a long time, it was believed that all somatic cells completely suppressed L1 activity by DNA methylation with patterns established during early gastrulation (Bestor and Bourc'his, ), differently from germinal cells which during gametogenesis could be permissive (Branciforte and Martin, ; Brouha et al ., ; Georgiou et al ., ). Currently, the conceptual model of L1 activity in the host somatic cell has changed in light of subsequent discoveries: (1) the detection of L1 activity, both in various types of cancer cells (Iskow et al ., ; Lee et al ., ; Tubio et al ., ) and in aging/senescent cells (De Cecco et al ., , , ); (2) the finding that healthy somatic cells can become permissive to L1 activity during certain developmental windows, including early embryogenesis (Prak et al ., ; Muotri et al ., ) and neurogenesis (Richardson et al ., ; Suarez et al ., ); (3) the observation that L1‐RTP occurs in cells responding to several environmental stresses (Ishizaka et al ., ; Ade et al ., ; Horváth et al ., ).…”
Section: Introductionmentioning
confidence: 99%